Use Less, Pay More: Can Climate Policy Address the Unfortunate Event for Being Poor? - Lucas Bretschger; Nujin Suphaphiphat (ETH Zurich, CER-ETH - Center of Economic Research, 2012)
The paper develops a two-region endogenous growth model with climate change affecting the countries' capital stocks negatively. We compare two different policies aimed at supporting less developed countries: climate mitigation by rich countries, which diminishes the increase in stock pollution and hence capital depreciation, and income transfers in the tradition of development aid. Under a mild set of assumptions we find that active climate policies are more efficient for rich economies and also, remarkably, better for poor countries than additional development aid. The main reason is the difference between the two policies with respect to their effects on economic growth. The results are robust with respect to possible model extensions.
Keywords: O10; Q52; Q54; 330; Climate policy; development aid; endogenous growth; stock pollution; Klimawandel; Kapitalstock; Klimapolitik; Entwicklungshilfe; Endogenes Wachstumsmodell; Zwei-Länder-Modell; Theorie